FACTORS AFFECTING THE QUALITY OF HEALTH SERVICES TO THE NUMBER OF PATIENT VISITS AT SIMARIMBUN HEALTH CENTER, SIANTAR MARIMBUN DISTRICT PEMATANG SIANTAR CITY - Ismi Noer Fadilah; Muharti Sanjaya; Wilson Samosir (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
05 means Ho is rejected, this indicates that nursing services have an effect on the quality of health services at the Simarimbun Health Center, Siantar Marimbun District, 2017. From the statistical test results, the probability value p (value) is 0.014-0.05, meaning Ho is rejected, this indicates that administrative services effect on the quality of health services at the Simarimbun Health Center, Marimbun District, in 2017. From the statistical test results, the probability value of p (value) is -0.000 if a is -0.05-0.000, then there is an effect of drug service on the quality of health services at the Simarimbun Health Center, Siantar District Marimbun 2017. Fulfillment of patient expectations for health services as an indicator of patient satisfaction in receiving health services is largely determined by attitude. doctor's behavior and ethics, paramedics and non-medical in providing health services to patients. For this reason, it is hoped that in the future the services of doctors, nurses and health facilities need to be optimized at the Simarimbun Health Center so that people's expectations for obtaining health services can be fulfilled.